The five-point test: reliability, validity and normative data for children and adults - Tucha, Lara; Aschenbrenner, Steffen (PLOS ONE, 2012)
The present study provides normative data from a sample of 257 healthy children and 608 adults on a modified version of the Five-Point Test (5PT). The 5PT is a structured and standardized test measuring figural fluency functions. Interrater reliability, test-retest-reliability and construct validity of this measure were analyzed. The sensitivity of the task for cognitive disturbances of patients with neurological diseases was proven by analyzing the test performance in the 5PT of patients with Parkinson's disease. Finally, normative data stratified by age and corrected for education level is provided. The results of the present study confirm the value of the 5PT in the measurement of figural fluency functions in clinical examination and neuropsychological research.